2016
DOI: 10.1111/nep.12664
|View full text |Cite
|
Sign up to set email alerts
|

FGF‐23 and Osteoprotegerin but not Fetuin‐A are associated with death and enhance risk prediction in non‐dialysis chronic kidney disease stages 3–5.

Abstract: Biomarkers are often associated with clinical endpoints, and we observed such associations in our study of patients with advanced CKD. However, the markers analysed in our study were of limited benefit in improving the prediction of these outcomes. Any extra information biomarkers may provide to improve risk prediction in clinical practice needs to be carefully balanced against the potential cost of these tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…[27][28][29] Eight studies reported associations that could not be extracted or reliably expressed as RRs comparing the top versus bottom third of baseline FGF-23 concentration (see Supplemental Table 4 for results from these and the other excluded studies). [30][31][32][33][34][35][36][37] Of 34 studies included in primary analyses, 17 were in predominantly general population cohorts, 22,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] nine were in patients with CKD not on dialysis, 23,[54][55][56][57][58][59][60][61] and eight in patients on dialysis 24,[62][63][64][65][66][67][68] ( Figure 1). For patients on dialysis, a single large trial (EValuation Of Cinacalcet HCl Therapy to Lower CardioVascular ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Eight studies reported associations that could not be extracted or reliably expressed as RRs comparing the top versus bottom third of baseline FGF-23 concentration (see Supplemental Table 4 for results from these and the other excluded studies). [30][31][32][33][34][35][36][37] Of 34 studies included in primary analyses, 17 were in predominantly general population cohorts, 22,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] nine were in patients with CKD not on dialysis, 23,[54][55][56][57][58][59][60][61] and eight in patients on dialysis 24,[62][63][64][65][66][67][68] ( Figure 1). For patients on dialysis, a single large trial (EValuation Of Cinacalcet HCl Therapy to Lower CardioVascular ...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies reported associations between FGF-23 and all-cause mortality: seven in a general population, 39,40,44,47,49,51,53 eight in a nondialyzed CKD population, 23,44,54,56,57,[59][60][61] and eight in a dialysis population. 24,[62][63][64][65][66][67][68] Overall, comparing participants in the top versus bottom third of baseline FGF-23 concentration, there was an increased risk of death from all causes (RR, 1.70; 95% CI, 1.52 to 1.91).…”
Section: Association Between Fgf-23 and Mortalitymentioning
confidence: 99%
“…This was a sub-study of the Salford Kidney Study, a single-centre, longitudinal, observational study of patients with stage 3 to 5 CKD referred to an adult secondary care nephrology outpatient clinic [25,26] .…”
Section: Methodsmentioning
confidence: 99%
“…When reviewing the full text of the remaining 283 articles, we excluded a further 264 additional articles, leaving 19 prospective studies17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 eligible for inclusion in the meta‐analysis. Patients were recruited on the basis of having diabetes mellitus in 2 studies, kidney disease in 7 studies, preexisting heart disease in 5 studies, and recent acute coronary syndromes in 5 studies.…”
Section: Resultsmentioning
confidence: 99%